1998
DOI: 10.1021/ma981216c
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Study of Different Types of Poly(vinyl formal)

Abstract: Several types of poly(vinyl formal) (PVF), copolymers of six-member formal rings and unreacted vinyl alcohol, prepared by different methods of synthesis out of atactic poly(vinyl alcohol) (PVA) were studied by NMR, thermal analysis, and wide-angle X-ray diffraction (WAXD). While thermal analysis and WAXD provide useful information about the macroscopic properties (e.g., T g, crystallinity, T m), solid-state NMR does focus more on the microscopic properties like molecular phase separation and molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In 1996, Matsuda and research team4 reported the UV irradiated surface grafting of PVA with pectic acid and alginic acid. PVA was modified with formaldehyde,5 carbamates,6 gallate,7 Ibuproven,8 glycosamines,9 phosphenanthrene derivatives,10 methyloil groups,11 polypropylene,12 fatty acids,13 poly(methacrylic acid),14 sodium benzoate,15 and docosanoic acid chloride 16. Rhim et al17 studied the poly(acrylic acid‐ co ‐maleic acid) crosslinked PVA with improved thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Matsuda and research team4 reported the UV irradiated surface grafting of PVA with pectic acid and alginic acid. PVA was modified with formaldehyde,5 carbamates,6 gallate,7 Ibuproven,8 glycosamines,9 phosphenanthrene derivatives,10 methyloil groups,11 polypropylene,12 fatty acids,13 poly(methacrylic acid),14 sodium benzoate,15 and docosanoic acid chloride 16. Rhim et al17 studied the poly(acrylic acid‐ co ‐maleic acid) crosslinked PVA with improved thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The DSC scans of PVF-1 and PVF-2 show a transition temperature around 81 and 87°C, respectively. Glass transition temperature of PVF increases with the increase of acetalization degree [38]. The variations of the dynamic mechanical properties with temperature for PVA, PVF-1 and PVF-2 are presented in Figure 3.…”
Section: Results and Discussion 31 Characterization Of Pvf-(12)mentioning
confidence: 99%
“…The PVFN-8 film spectrum (Figure 10a) evidences the intense absorption bands at 1709 and 1730 cm -1 attributed to C=O stretching from urethane, ester or imide groups, 1536 cm -1 (amide II), 1395 cm -1 (C-N-C), 1220 cm -1 (amide III) and 1159 cm -1 (C-O-C). The peak at 1776 cm -1 is attributed to the maleimide-furan cycloadduct [38]. The spectrum ATR-FTIR of PVFN-8 after heating at 150°C (Figure 10b) presents a shift of absorption band characteristic to C=O stretching from 1709 to 1711 cm -1 and the disappearance of the absorption bands at 1776 cm -1 attributed to the cycloadduct and at 1190 cm -1 corresponding to C-N-C (succinimide structure).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…9b), which provides more stable sixmembered ring acetals between formaldehyde and two neighboring hydroxyl groups of the intrachain. [54][55][56] PVF is almost completely swollen in DMF (Fig. 9b), whereas the swollen PVF-GA had clearly visible boundary (Fig.…”
Section: Absorption Kineticsmentioning
confidence: 99%